2013
DOI: 10.1523/jneurosci.4889-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Repetition Suppression and Multi-Voxel Pattern Similarity Differentially Track Implicit and Explicit Visual Memory

Abstract: Repeated exposure to a visual stimulus is associated with corresponding reductions in neural activity, particularly within visual cortical areas. It has been argued that this phenomenon of repetition suppression is related to increases in processing fluency or implicit memory. However, repetition of a visual stimulus can also be considered in terms of the similarity of the pattern of neural activity elicited at each exposure-a measure that has recently been linked to explicit memory. Despite the popularity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
76
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(86 citation statements)
references
References 48 publications
8
76
1
Order By: Relevance
“…Indeed, recent neuroimaging studies found that trials leading to behavioral priming also lead to fMRIa in the fusiform and occipital face areas (FFA and OFA) of the human brain . Similarly, repetition priming has also been related to fMRIa in several cortical areas for objects and scenes, including prefrontal, parietal, and occipito-temporal ones (Soldan et al 2010;Ward et al 2013). However, a clear causal relationship could not been determined between behavioral priming and RS as of today.…”
Section: Introductionmentioning
confidence: 97%
“…Indeed, recent neuroimaging studies found that trials leading to behavioral priming also lead to fMRIa in the fusiform and occipital face areas (FFA and OFA) of the human brain . Similarly, repetition priming has also been related to fMRIa in several cortical areas for objects and scenes, including prefrontal, parietal, and occipito-temporal ones (Soldan et al 2010;Ward et al 2013). However, a clear causal relationship could not been determined between behavioral priming and RS as of today.…”
Section: Introductionmentioning
confidence: 97%
“…These data suggest that the success of hippocampally mediated encoding of event details is influenced by, or at least covaries with, the strength or fidelityof the corresponding cortical representations. We expect that these, and other recent MVPA and RSA observations (Johnson et al 2009;McDuff et al 2009;Rissman et al 2010;Ward et al 2013), will be the first of many instances, in which the application of multivariate analytic techniques, combined with the spatial resolution of fMRI, allows researchers to make critical progress on open questions about the neurobiological mechanisms governing memory.…”
Section: Multivariate Fmri Analyses and Memory Theorymentioning
confidence: 82%
“…In particular, RSA analyses of fMRI encoding data suggest that, in some contexts, representational stability may be beneficial to later remembering (Xue et al 2010;Ward et al 2013; but see Wagner et al 2000), demonstrating that greater pattern similarity of an item's neural representations across multiple encoding trials predicts better subsequent memory for the item. Although some questions remain (Xue et al 2013;Davis et al 2014), researchers are now positioned to measure, at the individual trial level and within an individual human brain, the large-scale distributed neural representations that underlie important aspects of memory behavior.…”
Section: Multivariate Fmri Analyses and Memory Theorymentioning
confidence: 99%
“…5). It has been reported that IPL_L is involved in a goal-directing function, which causes repetition suppression in human studies181920 or the prediction repetition priming phenomenon21.…”
Section: Discussionmentioning
confidence: 99%